The womanist idea - Maparyan, Layli. (Contemporary sociological perspectives series., 2012)
"Following on the heels of The Womanist Reader, The Womanist Idea offers a comprehensive, systematic analysis of womanism, including a detailed discussion of the womanist worldview (cosmology, ontology, epistemology, logic, axiology, and methodology) and its implications for activism. From a womanist perspective, social and ecological change is necessarily undergirded by spirituality - as distinct from religion per se - which invokes a metaphysically informed approach to activism."--Publisher's website.